The 53rd Element - Dow Chemical Company (1938)
Color print advertisement for iodine manufactured by the Dow Chemical Company. The advertisement features a bottle of iodine and a manicured hand holding a dropper. A drop of iodine is illustrated against a plain background with the text "The 53rd Element." Accompanying text describes the benefits of iodine, as well as Dow Chemical's development of an iodine recovery method using oil well waste brine. The text notes that Dow Chemical was the first commercial producer of iodine in the United States.
Keywords: Dow Chemical Company; Advertising; Corporations; Iodine; Chemical industry; Chemical elements; Medical supplies; Antiseptics; Antiseptics in dentistry; Advertising, Industrial